1986
DOI: 10.1159/000173102
|View full text |Cite
|
Sign up to set email alerts
|

Nonanticoagulant Protective Effect of Heparin in Chronic Aminonucleoside Nephrosis

Abstract: Aminonucleoside nephrosis progresses over an 18-week period to focal and segmental glomerulosclerosis (FSGS). Whole heparin has been shown to blunt the extent of renal injury in another model of FSGS, renal ablation; however, the precise mechanism of protection has remained uncertain. Since heparin has a variety of physiologie actions unrelated to anticoagulation, we administered three different heparin compounds, each with a distinct profile of biological properties, to groups of rats given a single intraveno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
5

Year Published

1988
1988
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 9 publications
1
20
0
5
Order By: Relevance
“…This model also differs from that produced by adriamycin, which induces nephrotic syndrome but not severe renal insufficiency (35,36), and from other experimental glomerulonephritides (13,14), which feature renal insufficiency but not nephrotic syndrome. Interestingly, this model also differs from that which occurs using the same PA dosing regimen in Sprague-Dawley rats (1)(2)(3)(4), in that the Munich-Wistar rats exhibit markedly more severe renal insufficiency, morphologic injury, and nephrotic syndrome than do the apparently less susceptible Sprague-Dawley rats. Although initial (phase I) and recurrent (phase III) proteinuria and glomerular sclerosis are of comparable magnitude in the two strains, the SpragueDawley rat develops sclerosis much earlier, but with negligible tubulointerstitial abnormalities, suggesting differences in both susceptibility to, and sequellae after, acute injury between the two strains.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This model also differs from that produced by adriamycin, which induces nephrotic syndrome but not severe renal insufficiency (35,36), and from other experimental glomerulonephritides (13,14), which feature renal insufficiency but not nephrotic syndrome. Interestingly, this model also differs from that which occurs using the same PA dosing regimen in Sprague-Dawley rats (1)(2)(3)(4), in that the Munich-Wistar rats exhibit markedly more severe renal insufficiency, morphologic injury, and nephrotic syndrome than do the apparently less susceptible Sprague-Dawley rats. Although initial (phase I) and recurrent (phase III) proteinuria and glomerular sclerosis are of comparable magnitude in the two strains, the SpragueDawley rat develops sclerosis much earlier, but with negligible tubulointerstitial abnormalities, suggesting differences in both susceptibility to, and sequellae after, acute injury between the two strains.…”
Section: Discussionmentioning
confidence: 90%
“…Although more extreme, this hemodynamic pattern of decreased SNGFR, SNFF, and Kf is similar to that reported in nonnephrotic rats administered lower doses of PA (1 1, 12). 2 The role of reduced serum albumin and plasma oncotic pressure was further addressed in studies of four nephrotic rats which received normal plasma, rather than nephrotic plasma, to replace surgical losses during the experiment. In these rats, values for serum protein concentration were raised toward (5.0±0.3 g/dl) although not to normal levels.…”
Section: Resultsmentioning
confidence: 99%
“…Heparin treatment suppressed the formation of hypercellular mesangial nodules in the focal mesangio-proliferative disease induced by injecting Habu snake venom into rats (13). It also reduces the mesangial hypercellularity that develops in chronic aminonucleoside nephrosis (14), but it does not affect endocapillary proliferation in the progressive Masugi nephritis model (18). Particularly pertinent to this study, heparin has been shown to prevent albuminuria and mesangial expansion in diabetic rats (11,12) and to suppress mesangial cell proliferation and matrix expansion in experimental mesangio-proliferative glomerulonephritis (19).…”
mentioning
confidence: 87%
“…It is synthesized as a proteoglycan (serglycin) that is found in mast cells. Heparin has been shown to inhibit mesangial cell growth in both experimental renal disease models (11)(12)(13)(14)(15) and in cell culture (16,17). Heparin treatment suppressed the formation of hypercellular mesangial nodules in the focal mesangio-proliferative disease induced by injecting Habu snake venom into rats (13).…”
mentioning
confidence: 99%
“…Furthermore, the chronic phase of our glomerular nephritis model referred to above (28), in which there is mesangial cell proliferation, was prevented by administration of a nonanticoagulant, antiproliferative heparin derivative, as well as by whole heparin (42), and proteinuria was markedly diminished.…”
Section: Heparin and Vascular Smooth Muscle Proliferationmentioning
confidence: 88%